A new layered rock constitutive model incorporating confining pressure and bedding angle weights based on orthogonal matrix analysis - Liu, Haiyan; Zuo, Jianping; Topal, Erkan; Liu, Yanjun; Lei, Bo; Li, Danqi (Environmental earth sciences, 2024)
Under the combined influences of confining pressure, lithology and bedding, the deformation and failure characteristics of layered rocks become more complex posing a significant challenge in safe underground excavations. In this study, two groups of specimens were prepared with various bedding angles including 0°, 10°, 20°, 30°, and 45°. X-ray diffraction and scanning electron microscopy were employed to analyze the mineral composition and internal microstructures of the specimens. Triaxial compression tests were conducted on the specimens subject to different confining pressures. Then, orthogonal matrix analysis was utilized to determine the specific influence weights of confining pressure, lithology, and bedding on peak differential stress, elastic modulus and peak strain of the rock samples. Finally, by implementing the proposed weight matrix, a statistical damage constitutive model for the layered rock under the coupled effects of confining pressure, lithology, and bedding was developed. It was found that the peak stress difference, cohesion, and internal friction angle decrease as the bedding angle increases, while the elastic modulus increases with the bedding angle. Additionally, the two groups of specimens exhibited distinct failure patterns under the influence of bedding angle and confining pressure. The averaged influence weights of confining pressure, lithology, and bedding on the rock deformation and failure characteristics are 40.99%, 23.87%, and 35.14%, respectively. The analytical simulation results were validated with the experimental results in this study and literature confirming the capability of the proposed constitutive model for capturing the stress–strain behavior of layered rock with various bedding angles subject to different confining pressures.